2018
DOI: 10.1021/jacs.8b05544
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Screening of Lanthipeptide Analogs via In-Colony Removal of Leader Peptides in Escherichia coli

Abstract: Most native producers of ribosomally synthesized and post-translationally modified peptides (RiPPs) utilize N-terminal leader peptides to avoid potential cytotoxicity of mature products to the hosts. Unfortunately, the native machinery of leader peptide removal is often difficult to reconstitute in heterologous hosts. Here we devised a general method to produce bioactive lanthipeptides, a major class of RiPP molecules, in Escherichia coli colonies using synthetic biology principles, where leader peptide remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 33 publications
(93 reference statements)
1
45
0
Order By: Relevance
“…Enzymatic modification in lanthipeptides, and most RiPPs, is unusual because changes made to the core peptide sequence are often tolerated by the modifying enzymes provided the leader peptide sequence is kept invariable [8,9]. This separation of substrate recognition in the leader peptide and catalysis on the core peptide has greatly facilitated combinatorial approaches to assess structure-activity relationships [21][22][23][24][25] and bioengineering efforts [26][27][28][29][30][31][32] with lanthipeptides. Unsurprisingly, nature has also used this substrate tolerance for the generation of diversity at low genetic cost as discussed in this review.…”
Section: Trends Trends In In Chemistry Chemistrymentioning
confidence: 99%
“…Enzymatic modification in lanthipeptides, and most RiPPs, is unusual because changes made to the core peptide sequence are often tolerated by the modifying enzymes provided the leader peptide sequence is kept invariable [8,9]. This separation of substrate recognition in the leader peptide and catalysis on the core peptide has greatly facilitated combinatorial approaches to assess structure-activity relationships [21][22][23][24][25] and bioengineering efforts [26][27][28][29][30][31][32] with lanthipeptides. Unsurprisingly, nature has also used this substrate tolerance for the generation of diversity at low genetic cost as discussed in this review.…”
Section: Trends Trends In In Chemistry Chemistrymentioning
confidence: 99%
“…The extent to which GFP can function as a fusion partner for heterologous expression of cationic, hydrophobic peptides with toxic effects to E. coli, should be further explored. Recently, it has been demonstrated that class I and class II lanthipeptides can still undergo posttranslational modification while fused to the C-terminal of GFP (Ongey et al, 2018;Si et al, 2018;Van Staden et al, 2019). These studies further promote fusion to GFP as an elegant approach to improve the heterologous expression of modified or unmodified cationic, hydrophobic peptides in E. coli while maintaining their bioactivity.…”
Section: Resultsmentioning
confidence: 99%
“…One notable advantage of this in cis fusion design is that there is no need for the proteolytic removal of the leader peptide from the modified peptide to give rise to the final product. Indeed, substantial engineering efforts are often required to facilitate the late leader removal by installing the digestion site of well-characterized, commercially available proteases or unnatural amino acids immediately upstream to the core peptide ( Bindman et al., 2015 ; Si et al., 2018 ). The leader removal remains a challenge in the biocatalytic synthesis of RiPP analogues.…”
Section: Biocatalytic Approaches For the Synthesis Of Rippsmentioning
confidence: 99%
“…Bioactivity testing is performed by measuring fluorescent signal that positively correlates with the biomass of sensor cells. A similar growth-inhibition-based high-throughput screening method was also developed recently by the Zhao and van der Donk groups in engineering the lanthipeptide library ( Si et al., 2018 ).…”
Section: Biocatalytic Approaches For the Synthesis Of Rippsmentioning
confidence: 99%